Media Global Dalam Perjuangan Perempuan Untuk Kesetaraan Gender Di Afghanistan: Analisis Komunikasi Berbasis Interseksionalitas - Helen Afriliyanti; Tina Kartika; Marizka Andyanita (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
This article examines how global media plays a role in Afghan women’s struggle for gender equality, employing an intersectionality approach and Fairclough’s critical discourse analysis. Since the Taliban's takeover of Afghanistan in August 2021, women's rights in the country have faced severe restrictions, including bans on women's education and limitations on mobility. The article focuses on how these restrictions exacerbate gender inequality and create additional challenges for women, especially those from ethnic minority groups such as the Hazara. On the other hand, global media often portrays Afghan women as victims, despite notable efforts of protest and resilience by the women themselves. Using Kimberlé Crenshaw’s intersectionality theory, this article explores how Afghan women’s experiences are shaped by various intersecting factors of oppression, such as gender, ethnicity, and socio-economic status. Furthermore, Fairclough’s critical discourse analysis is applied to understand how global media constructs narratives about Afghan women and how these narratives contribute to the international discourse on women’s rights in Afghanistan. The findings of this study highlight the importance of global solidarity, the role of social media, and the involvement of the Afghan diaspora in raising issues about women in Afghanistan, although significant challenges to achieving concrete change remain.